Analysis of Suitability and Supporting Capacity of Sasak Beach Tourism Pasaman Barat - Fikri Andrian; Rifaldi Rifaldi; Elizal Elizal (Jurnal Perikanan dan Kelautan, 2022)
This research was conducted in February 2021 at Sasak Beach, West Pasaman Regency, West Sumatra Province, aiming and the benefit of this study is to examine the suitability of beach tourism in Sasak Beach based on biophysical aspects, including the precept of the community to ecotourism activities in Sasak Beach, as well as analyze the supporting factors of its activities. The method used in the study is a method of surveying directly to the research site and measuring the necessary data qualitatively and quantitatively The goal is to get information about Sasak Beach and the perspective of tourists on the development of marine ecotourism at the research site. Sasak Beach has a specific feature with the planting program of a thousand pine trees. This beach has great potential and opportunities to be developed as a beach tourism area The highest conformity values are found in station I, and the lowest are in stations II and III. This value makes Sasak Beach can be used as a marine ecotourism.